Stress sensing with Co based ferrite composites - Pasquale, M; Sasso, CP; Velluto, M; Lim, SH (ELSEVIER SCIENCE BV, 2002)
We measure the magnetic and magneto-mechanical properties of polymer-bonded Co ferrites to analyze their behavior as stress sensors in a wide temperature and compressive range. The composites possessing a magnetostriction of 30x 10(-6) and a Young's modulus of 5 GPa are good candidates for a range of sensing applications. with good chemical stability and good high frequency characteristics. (C) 2002 Elsevier Science B.V. All rights reserved.